Accounting Capability and MSMEs’ Access to Government Programs in the TTU-Oecusse Border Region - Margareta Diana Pangastuti; Ernestina Lika; Bernadus Ghawa Rado (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the effect of accounting capability comprising accounting literacy, financial record-keeping practices, and the use of accounting information on Micro, Small, and Medium Enterprises (MSMEs) access to government programs in the Indonesia-Timor Leste border region, particularly in the North Central Timor Regency. Methodology: This study employs a quantitative explanatory approach using data from 100 MSME actors selected through purposive sampling in Indonesia. The data were analyzed using multiple linear regression to assess the partial and simultaneous effects of each dimension of accounting capability on access to government programs. Results: The findings indicate that all dimensions of accounting capability positively and significantly affect MSMEs’ access to government programs. Among these, financial record-keeping practices emerged as the most dominant factor, highlighting the critical role of practical financial management. Conclusions: Accounting capability plays a crucial role in enhancing MSMEs’ integration into public policy systems in border regions. In particular, the ability to maintain consistent financial records is more decisive than conceptual understanding or information utilization. Limitations: This study is limited to the border area of North Central Timor Regency and the Oecusse enclave of Timor Leste and does not incorporate other influencing factors, such as technological access and institutional support. Contributions: This study contributes to the literature by integrating Institutional Theory and the Resource-Based View to explain MSMEs’ access to government programs. It also provides context-specific empirical evidence from a border region, offering policy-relevant insights for improving MSME inclusiveness and sustainability.